The Phenomenon of Rat Mouse-like Body Structure in Mammals - MILJUTIN, ANDREI (University of Tartu Press, 2023)
This book introduces the most ancient and commonest mammalian life form, which is nonetheless largely overlooked - the muridoids, i.e., animals with mouse-like body structure. There are approximately two thousand mouse-like species, or about a third of all mammals, belonging to 9 different orders. The author explains the reason for the existence of mouse-like body structure, describes the taxonomic, morphological, ecological and ecomorphological diversity of mouse-like animals, and reveals the role of muridoids in the evolution of mammals.